Port-site implantation of parasitic leiomyoma after laparoscopic myomectomy and its histopathology. (September 2020) - Kai, Kentaro; Aoyagi, Yoko; Nishida, Masakazu; Arakane, Motoki; Kawano, Yasushi; Narahara, Hisashi
Although parasitic leiomyoma could be spontaneous or iatrogenic in origin, port-site implantation of parasitic leiomyoma is an iatrogenic benign sequela of laparoscopic surgery. A 30-year-old, primigravida Japanese woman was referred after unresponsiveness to preoperative gonadotropin-releasing hormone for intramural fibroids. Magnetic resonance imaging showed multiple intramural fibroids and left ovarian endometrioma with no malignant features. Laparoscopic myomectomy with power morcellation and ovarian cystectomy were performed, followed by treatment with a combined oral contraceptive. Seven years after the primary surgery, she underwent abdominal myomectomy for a port-site, and peritoneal recurrence of the leiomyoma and intramural leiomyomas was detected. Microscopic examination revealed that resected specimens from the port-site demonstrated leiomyoma with lesser cell density and more prominent hyalinization than those from the uterus. Therefore, clinicians should counsel patients regarding the risks and benefits of laparoscopy with morcellation versus laparotomy. Further development of techniques for uterine tissues extraction is warranted.